Предмет: Алгебра,
автор: alya2471
преобразуйте выражение а)(y-4)^2 б)(5c+1)(5c-1)
2)Вычислите а)17^2-34×7+7^2 б)67^2-33^2/25^2-15
решите прошу
Ответы
Автор ответа:
12
Решение:
1.
а) (y - 4)² = у² - 8у + 16
б) (5c + 1) (5c - 1)= 25с² - 1
2.
а) 17² - 34 · 7 + 7² = (17 - 7)² = 10² = 100
б) (67² - 33²) : ( 25² - 15²) = (67 + 33)(67 - 33) : ((25 + 15)(25 - 15)) =
= 100 · 34 : (40 · 10) = 3 400 : 400 = 8,5
Похожие вопросы
Предмет: Русский язык,
автор: yurash
Предмет: Русский язык,
автор: yurash
Предмет: Английский язык,
автор: Margo1311
Предмет: Музыка,
автор: serezhenka12